Screening Kesehatan (Gigi, Mulut, Mata, Telingga) Pada Anak Sekolah Dasar: Health Screening (Dental, Oral, Eye, Ear) for Elementary School Children - Ristanto, Riki; Kunto Adi Patria, Dion (Chakra Brahmanda Lentera Institute, 2025)
Habits such as eating patterns, personal hygiene, and unhealthy snacking can affect students' health at school. To prevent these risks, health screening becomes an important step. ITSK RS Dr. Soepraoen Malang organized a health screening at SDN Dusun Sumber Bendo, Kucur Village, Dau District, Malang Regency, to detect issues with students' teeth, mouth, eyes, and ears. The activity was carried out in several stages. During the preparation phase, the community service team obtained permits from LPPM ITSK Soepraoen and the Head of SDN 9 Dusun Sumber Bendo. The team then divided tasks into two groups: one arranged the activity location, while the other prepared logistics, including borrowing equipment from the DIII Nursing Program laboratory and providing stationery and refreshments. The activity took place on May 11, 2024, and involved three groups: student guidance, administration, and screening. The guidance group managed the activity flow, the administration group recorded students' data, and the screening group conducted examinations at six stations. A total of 55 students from grade 1 of SDN 9 Dusun Sumber Bendo participated, from 08:00 to 11:00 WIB. The health screening results showed that only the tongue examination had a 100% normal result. The majority of students had cavities (51%) and caries (35%), with the highest cases found among female students (56%). For tonsil health, two students in grade 5 (4%) had tonsillitis. The eye examination revealed that 12 students (22%) had myopia, and 2 students (4%) had partial color blindness. Ear examinations often showed the presence of little (38%) or a lot of earwax (35%), with higher numbers in female students. These issues highlight the need for increased attention to dental and ear health, with education and routine examinations that can help prevent health problems that may impact children's learning process.